Common fixed points of single-valued and multivalued maps - Yicheng Liu; Jun Wu; Zhixiang Li (International Journal of Mathematics and Mathematical Sciences)
We define a new property which contains the property (EA) for a hybrid pair of single- and multivalued maps and give some new common fixed point theorems under hybrid contractive conditions. Our results extend previous ones. As an application, we give a partial answer to the problem raised by Singh and Mishra.